Pornography Use and Sexual Coercion: Examining the Importance of Frequency, Type, and Other Factors - Marshall, Ethan A. (Journal of interpersonal violence, 2024)
Research on pornography use and sexual coercion has provided some evidence that there is an association between these two behaviors. One area in this body of research where there is a need for improvement is the operationalization of pornography use. In particular, a need for researchers to capture all relevant aspects of pornography use that are associated with sexual coercion. These aspects include frequency of use, type of pornography used, investment in use, sexual scripts adopted from pornography, compulsive use, and first exposure. The current study aims to examine which of these aspects of pornography use are significantly associated with sexual coercion. A sample of 365 college males was surveyed on their pornography use, engagement in sexually coercive behaviors, and other relevant variables. Results show that sexual scripts and investment in pornography use are significantly related to self-reported sexual coercion. These findings indicate that the frequency with which someone views pornography may not be driving the relationship between pornography use and sexual coercion and that an individual’s monetary investment in their pornography use habit, as well as their adoption of sexual scripts from pornography, may be what is driving this relationship. In addition, these findings have implications for the aspects of pornography use that researchers should focus on when examining the relationship between pornography use and sexual coercion.